Evaluating Health Outcomes for Children with Asthma and Determining the Role of Prevention and Health Education (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Asthma is the most common chronic respiratory disease in children. Notably, 80% of children's first asthma attacks occur before the age of 5, typically during preschool years. This aligns with trends in developed countries in Europe and the United States. This study aimed to evaluate health outcomes for children with asthma and determine the role of prevention and health education. The study included 90 patients, and all necessary written consent was obtained to ensure transparency and privacy. The study was conducted from 2024 to 2025 from several different hospitals in Iraq.The results showed that the most common age group with asthma was between 5 and 9 years old (40 patients, representing 44.4%). Patients were distributed equally according to gender: Male 45% 50%, Female 45% 50%. The average duration of asthma was 4.5 ± 2.1 years. Family history showed that 40 patients, the rate satisify were 44.4%and we concluded Although local and international research on the high use of corticosteroids in preschool children with asthma is limited, the relationship between corticosteroids and asthma in children has been explored. Studies have revealed that nearly half of primary school children with asthma use corticosteroids, which affects their mood and interpersonal relationships. A comparison between students with asthma and healthy students concluded that students with asthma reported lower performance in physical activities and greater difficulty learning physical education.